Exploring the attitudes of undergraduate college students in Egypt towards English - Marwa Mohamed Hassan Hedia (Insights into Language, Culture and Communication, 2022)
This paper attempts to identify the attitudes of undergraduate university students in Egypt towards the emergence of English as a global language and as an international language in scientific domains. A total of 54 Engineering and Business students from an English-medium university participated in the study during the academic year 2018-2019. In order to answer the research questions, the study employed two main tools: questionnaires and interviews. SPSS package was used to statistically analyze quantitative data while qualitative data obtained from students' responses in interviews was investigated using content analysis. Results show that most students hold positive attitudes towards English and view it as a unifying tool that facilitates communication across the world. The paper concludes with a call for the application of critical pedagogy (CP) in the practice of ESP and EAP in order to address questions of linguistic and cultural identity. The researcher hopes to encourage curriculum developers and educators to raise students’ awareness towards the complex ideological and social choices they face in learning and using English.